2022
DOI: 10.1002/hep4.2038
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in the proprotein convertase gene furinb causes hepatic cystogenesis during liver development in zebrafish

Abstract: Hepatic cysts are fluid-filled lesions in the liver that are estimated to occur in 5% of the population. They may cause hepatomegaly and abdominal pain.Progression to secondary fibrosis, cirrhosis, or cholangiocarcinoma can lead to morbidity and mortality. Previous studies of patients and rodent models have associated hepatic cyst formation with increased proliferation and fluid secretion in cholangiocytes, which are partially due to impaired primary cilia.Congenital hepatic cysts are thought to originate from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Rather, we identified biological processes previously found to be important in biliary development, repair, and cystogenesis; GO terms associated with cytoskeleton remodeling and cell matrix adhesion (30,31), namely, transforming growth factor-β (TGFβ) (32) and integrin (33) signaling, were changed (Fig. 1I and data file S2), adding further support to the idea that alterations in the extracellular matrix (ECM) (34) and cytoskeletal dynamics, in addition to induction of known cystogenic signaling signatures, promote the generation of cysts in vivo (35,36).…”
Section: Loss Of Primary Cilia Results In Tissue Remodeling To Form T...mentioning
confidence: 70%
“…Rather, we identified biological processes previously found to be important in biliary development, repair, and cystogenesis; GO terms associated with cytoskeleton remodeling and cell matrix adhesion (30,31), namely, transforming growth factor-β (TGFβ) (32) and integrin (33) signaling, were changed (Fig. 1I and data file S2), adding further support to the idea that alterations in the extracellular matrix (ECM) (34) and cytoskeletal dynamics, in addition to induction of known cystogenic signaling signatures, promote the generation of cysts in vivo (35,36).…”
Section: Loss Of Primary Cilia Results In Tissue Remodeling To Form T...mentioning
confidence: 70%
“…By whole genome sequencing, it was found that cyst formation in a mutant Zebrafish phenotype occurs due to missense mutations in the FURIN gene, which encodes for a proprotein convertase. This mutation causes a change in Furin protein localization and ER stress [ 44 ].…”
Section: Er Stress Response In Liver Diseasesmentioning
confidence: 99%
“…Hepatic cysts can be treated by ER stress inhibitors like 4-phenyl butyric acid or by mTOR inhibitors such as rapamycin [ 44 ]. It has also been found that polyunsaturated fatty acids (PUFA) have anti-inflammatory properties which protect liver cells from the toxicity induced by bile acids [ 118 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%